Healthy diets can create environmental trade-offs, depending on how diet quality is measured. - Conrad, Zach.; Blackstone, Nicole Tichenor.; Roy, Eric D. (Tufts University. Tisch Library., 2020)
Keywords: Diet quality, Sustainability, HEI, AHEI, NHANES, Waste.; Springer Open.